SLE-DAS in the First Trimester of Gestation Predicts Maternal Lupus Flares Later in Pregnancy - Maddalena Larosa; Maddalena Larosa; Maddalena Larosa; Nathalie Costedoat-Chalumeau; Nathalie Costedoat-Chalumeau; Nathalie Costedoat-Chalumeau; Gaëlle Guettrot-Imbert; Gaëlle Guettrot-Imbert; Veronique Le Guern; Veronique Le Guern; Nathalie Morel; Nathalie Morel; et al. (Frontiers Media S.A., 2021)
Introduction: Systemic Lupus Erythematosus (SLE) mainly occurs during childbearing age. Remission or low disease activity state (LDAS) before conception are recommended by experts to achieve a favourable lupus pregnancy outcome but little is known on the best way to evaluate remission or activity status during pregnancy.Objectives: We tested SLE-disease activity score (SLE-DAS) in the first trimester as predictor of maternal flares and obstetrical complications in 2nd and 3rd trimester in a cohort of SLE pregnant women.Patients and Methods: Inclusion criteria were: 1) women ≥ 18 years; 2) affected with SLE (SLICC 2012); 3) enrolled in two referral centers (Italy and France) 4) with an ongoing singleton pregnancy at 12 weeks (only one pregnancy per patient). Disease activity was assessed at first trimester of pregnancy, using SLE-pregnancy disease activity index (SLEPDAI) and retrospectively applying SLE-DAS. Maternal lupus flares at 2nd and 3rd trimester were defined by the SELENA-SLEDAI Flare Index (SFI). Adverse pregnancy outcome (APO) included: fetal and neonatal death, placental insufficiency with premature delivery <37 weeks, and small for gestational age (SGA) (≤3rd percentile).Results: We included 158 pregnant patients affected with SLE. At first trimester the median SLEPDAI (IQR) was 2 (0-4) and the median SLE-DAS (IQR) 1.32 (0.37-2.08). At least one flare occurred in 25 (15.8%) women during the 2nd and 3rd trimester. APO occurred in 19 (12.0%) patients. A significant correlation between SLE-DAS and SLEPDAI was found in this cohort (Spearman's ρ = 0.97, Figure 1). At multivariate analysis, both SLE-DAS and SLEPDAI predicted maternal flares (adjOR = 1.2; 95% CI = 1.0-1.3, p = 0.02; adjOR 1.3, 95% CI = 1.1-1.6 per unit increase, p = 0.01, respectively). SLE-DAS and SLEPDAI were associated with APO at univariate analysis (p = 0.02).Conclusions: SLE-DAS was highly correlated with SLEPDAI and its use in the first trimester predicted maternal flares in the 2nd and 3rd trimester, making SLE-DAS a reliable instrument to measure SLE activity during pregnancy.